The contributions of foreign aid and natural resource wealth to democratic institutions: Evidence from over 40 years of sub-Sahara Africa's history - Alex O. Acheampong; John Taden (Journal of Government and Economics)
This study evaluates the influence of natural resource rents and foreign aid on democracy using panel data from 45 SSA countries from 1980 to 2021. Using five different democracy indices, six different foreign aid variables and six different natural resource rent variables, our endogeneity-corrected results establish the following conclusions: (i) all the democracy indices respond positively and significantly to multilateral foreign aid, total development assistance committee (DAC) aid and bilateral aid from Australia, the USA, the United Nations, and the European Union (ii) the political resource curse, rentier and repression theories are valid for rent from mineral, gas and oil resources (iii) the democracy indices respond positively and significantly to rent from coal and forest resources (iv) the effect of foreign aid on the democracy indices is contingent on natural resource wealth (v) these findings are robust to an alternative econometric estimation technique and specifications. The policy implications are discussed.